PENGARUH PARAMETER PROSES SLICING SOFTWARE TERHADAP KEKASARAN PERMUKAAN PRINTING PART MENGGUNAKAN FILAMEN ST-PLA - Yudha Bika Pratama; Pristiansyah; Hasdiansah Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
3D printer technology is often said to have a bright future, until now rapid prototyping technology is still developing into technology that is support for fields that support humans for technological advancement in order to bring what is imagined into a more tangible form. The purpose of this study is to determine the effect of parameters on surface roughness and an optimum parameter settings that produce minimal roughness. The taguchi method with an orthigonal matrix L25 (56). Was used in this study. The parameters to be analyzed in this study were layer thickness, printing speed, nozzle temperature, orientation, flow rate and cooling speed. To overcome the noise parameter (disturbance), the process of measuring the surface roughness of the specimen was carried out with 3 replications. Furthermore, the parameters will be analyzed using taguchi method which the smaller characteristic is the better parameter. Based on the results the sequence of parameters that have the greatest and smallest effect on surface roughness on ST-PLA filaments were obtained, namely the thicken layer, flow rate, Nozzle temperature, Printing speed, Cooling speed and Orientation. Setting parameter that produceS minimum roughness value with a value of 3.321 µm is 0.10 mm for coating thickness, 40 mm / s for print speed, 190?C for nozzle temperature, 45? for orientation, 110% for flow rate and 20% for cooling speed.